Adsorpsi Ion Logam Cu Dengan Menggunakan Fly Ash Sawit Sebagai Adsorben - Agustinus Lamhot Viraro; Edy Saputra; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Copper is one of the heavy metals that can cause environmental pollution. One method of separation that can be done to reduce the environmental pollution is adsorption method. With this method required an effective adsorbent to adsorb metalions. This research aims to Fly ash absorbent of copper. determine (1) under optimum conditions (time and pH) and Cu2+ ions adsorption using fly ash, (2) ion adsorption capacity of C2+ using fly ash, were analyzed using Atomic Absorption Spectrophotometer (AAS). Data were analyzed descriptively reported in tables and graphs. The results showed that the optimum contact time required for adsorption Cu2+ ions using fly ash is 60 minute and the optimum pH is 6. Cu2+ ion adsorption by the fly ash Freundlich adsorption isotherm according to the value of R2 = 0,973 mg/gKata kunci : Adsorption, Copper , Isothermal adsorption, fly ash